2001
DOI: 10.1590/s0037-86822001000200004
|View full text |Cite
|
Sign up to set email alerts
|

Estudo epidemiológico da leptospirose bovina e humana na Amazônia oriental brasileira

Abstract: The seroprevalence study for leptospirosis in bovines and humans was realized in family holder farms along the Transamazon Highway. The prevalence of bovine leptospirosis was 97% [90.9 - 99.5%] of farms with at least one positive animal according to microscopic agglutination test for the leptospirosis diagnostic. In 61.2% of the tested herds, the serovar hardjo was the most common, followed by the serovar bratislava (9%) and the serovar shermani (4.5%). The serologic prevalence of leptospirosis in humans was 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
1
24

Year Published

2007
2007
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(43 citation statements)
references
References 24 publications
2
8
1
24
Order By: Relevance
“…Seroagglutination tests showed that bovines reacted positively (45.6%) to serovar Hardjo according to Langoni et al (2008). Homem et al (2001), researching humans and other animals in Amazonia, observed that serovar Hardjo was the most prevalent. Bovine leptospirosis is endemic in Brazil and may cause abortions, infertility, anorexia, jaundice, hemoglobinuria, mastitis and even death (Santa Rosa et al 1972, Silva 1976, Simpson 2002, Langoni et al 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Seroagglutination tests showed that bovines reacted positively (45.6%) to serovar Hardjo according to Langoni et al (2008). Homem et al (2001), researching humans and other animals in Amazonia, observed that serovar Hardjo was the most prevalent. Bovine leptospirosis is endemic in Brazil and may cause abortions, infertility, anorexia, jaundice, hemoglobinuria, mastitis and even death (Santa Rosa et al 1972, Silva 1976, Simpson 2002, Langoni et al 2004).…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence of leptospirosis depends on: a host which is the disseminator of Leptospira, the environmental contamination with live leptospires, the survival of these bacteria in this environment and the contact of susceptible individuals with the agent (2,19). For the serovars to be adapted and maintained by bovines, direct transmission is a very important factor and seems to be independent of the region and climatic conditions, although dependent on herd management conditions, with transmission between bovines favored by intensive cattle production (12,22).…”
Section: Discussionmentioning
confidence: 99%
“…The genotype Hardjobovis is also associated with chronic renal infections in bovines and genotype Hardjoprajitno is most commonly associated with reproductive problems (12). Recent studies in Brazil show Hardjo (Hardjoprajitno and Hardjobovis) and Wolffi as the most reactive serovars in bovine herds (4,14,19,22,27,37). Some animal species which have been cited as accidentally infected by serovar Hardjo are capybara, deer, bubaline, equine, ovine, swine and man (5,15,23,29).…”
Section: Discussionmentioning
confidence: 99%
“…Investigações efetuadas em diferentes regiões do Brasil comprovaram prevalências em rebanhos bovinos que variam de 74 a 100% e, em animais, de 45,56 a 62,30% (Langoni et al, 2000;Favero et al, 2001;Homem et al, 2001;Lage et al, 2007). Diversas pesquisas constataram os sorovares Hardjo, Wolffi, Pomona, Grippotyphosa, Icterohaemorrhagiae e Canicola entre os mais frequentes, sendo o Hardjo o mais comum em bovinos.…”
Section: Introductionunclassified